2017
DOI: 10.7150/jca.17210
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of UGT1A1*28 Polymorphism In Irinotecan-based Chemotherapy

Abstract: The UGT1A1*28 polymorphism was suggested to be significantly connected with irinotecan-induced toxicity and response to chemotherapy. However, the results of previous studies are controversial. Hence we carried out a meta-analysis to investigate the effect of UGT1A1*28 polymorphism on severe diarrhea, neutropenia, and response of patients who had undergone irinotecan-based chemotherapy. The PubMed, Web of Science, Wanfang, and CNKI databases were searched for clinical trials assessing the association of UGT1A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
(37 reference statements)
0
31
0
2
Order By: Relevance
“…Many studies have shown that UGT1A1*28 is significantly associated with CPT-11-induced toxicity, especially neutropenia 2024. Caucasians with mutant genotypes are more likely to have neutropenia 12. However, UGT1A1*6 is more prevalent in Asian countries than in Caucasian populations, suggesting that UGT1A1*6 polymorphisms should be considered in addition to UGT1A1*28 polymorphisms for more individualized CPT-11-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown that UGT1A1*28 is significantly associated with CPT-11-induced toxicity, especially neutropenia 2024. Caucasians with mutant genotypes are more likely to have neutropenia 12. However, UGT1A1*6 is more prevalent in Asian countries than in Caucasian populations, suggesting that UGT1A1*6 polymorphisms should be considered in addition to UGT1A1*28 polymorphisms for more individualized CPT-11-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have found no correlation between different UGT1A1 genotypes and clinical efficacy 30,31. Further, a meta-analysis of 6,087 patients found that both homozygous and heterozygous UGT1A1*28 mutant types had a higher response than wild-type patients, particularly Caucasians 12. In our study, we observed that the tumor response in patients with UGT1A1*28 mutant genotypes with colorectal cancer was better than in those with the wild-type genotype; however, the difference was not statistically significant ( P =0.178).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rs4148323 is an intron variant of the UGT1A1 gene on human chromosome 2q37, which encodes a UDP‐glucuronosyltransferase, an enzyme of the glucuronidation pathway (Sugatani et al, ). It plays an important role in catalyzing the formation of bound bilirubin by unbound bilirubin (Liu, Lu, et al, ). Clinical studies have found that cancer patients carrying the GG genotype may reduce the risk of thrombocytopenia (Han, Lim, Park, Lee, & Lee, ) or diarrhea (Takekuma et al, ) when treated with irinotecan‐based regimens and may also increase tumor response, progression‐free survival Period or overall survival compared with patients with AA or AG genotype.…”
Section: Discussionmentioning
confidence: 99%